A study of some socio-economic factors related to adherence to Christian social values of high school seniors in twelve Benedictine schools - Valdez, M. Guadalupe F. (Animo Repository, 1977)
Five specific Christian social values and some socio-economic factors were investigated in the present study to ensure whether these two sets of variables are related. The specific Christian social values are: devotion to truth, moral responsibility, moral equality, brotherhood and respect for the human person. The definite socio-economic factors taken are: place of origin, residence while studying, family composition, parents' education, parents' occupation and family income. The rank order of the five Christian social values was also discovered. The population of the study was 1,496 high school senior students of the school year 1975-1976 enrolled in twelve Benedictine schools run by the Missionary Benedictine Sisters of Tutzing. The ACUP Research Survey Questionnaire in its entirety was administered to 449 high school seniors chosen by random sampling. The data gathered were then processed and computed For the analysis of Christian social values, the statistical tools used were the mean, standard deviation, standard error of the mean and the .05 level of significance. The relationship of the rankings of Christian social values made use of the Kendall Coefficient of Concordance: W. To test the relationship between the Christian social values and the socio-economic factors, the difference between means were computed using the Z-test for large samples and the Chi-Square test. The critical ratios were then obtained and compared with the tabulated ratios, which are found in statistical books.